1984
DOI: 10.1099/0022-1317-65-2-397
|View full text |Cite
|
Sign up to set email alerts
|

A Structural Investigation of the Epstein--Barr (EB) Virus Membrane Antigen Glycoprotein, gp340

Abstract: SUMMARYEpstein-Barr (EB) virus membrane antigen (MA) glycoprotein (gp340) purified by a molecular weight-based technique has been subjected to biochemical analysis. Following treatment with glycosidases or tunicamycin during synthesis, the carbohydrate moiety was found to be made up of both O-linked and N-linked types and to constitute about 50~o of the molecular mass. Digestion studies with neuraminidase and oligosaccharidase have indicated that the molecule is heavily sialated with most of the sialic acid lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
16
0

Year Published

1984
1984
1995
1995

Publication Types

Select...
5
4

Relationship

3
6

Authors

Journals

citations
Cited by 42 publications
(17 citation statements)
references
References 20 publications
1
16
0
Order By: Relevance
“…This protein together with gp95 and gp 130 produces characteristic diffuse bands on polyacrylamide gels which may indicate microheterogeneity within the polysaccharide moieties. A similar high molecular weight glycoprotein, which contains a high proportion of carbohydrate and which plays a major role in the host response to virus infection, has been isolated and characterized from cells transformed with Epstein-Barr virus (Morgan et al, 1984). Our results regarding gp52, gp67, gp95 and gp130 agree well with the data of Nowak et al (1984) who used radiolabelled concanavalin A to detect glycoproteins with mol.…”
Section: Discussionsupporting
confidence: 80%
“…This protein together with gp95 and gp 130 produces characteristic diffuse bands on polyacrylamide gels which may indicate microheterogeneity within the polysaccharide moieties. A similar high molecular weight glycoprotein, which contains a high proportion of carbohydrate and which plays a major role in the host response to virus infection, has been isolated and characterized from cells transformed with Epstein-Barr virus (Morgan et al, 1984). Our results regarding gp52, gp67, gp95 and gp130 agree well with the data of Nowak et al (1984) who used radiolabelled concanavalin A to detect glycoproteins with mol.…”
Section: Discussionsupporting
confidence: 80%
“…The concentration of continuous B cell epitopes in this amino-terminal domain may imply that this region is not concealed in the native gp340 molecule either as a result of protein folding or glycosylation (Morgan et al, 1984). The majority of epitopes defined above do not appear to be important in virus neutralization but could have some role in controlling the outcome of EBV infection by acting as targets in the membrane of lytically infected cells for ADCC or complement fixation (Beisel et al, 1985;Jondal, 1976;Qualti6re et al, 1982;Khyatti et al, 1991 ;Sairenji et al, 1991).…”
Section: Discussionmentioning
confidence: 99%
“…The efficacy of subunit antiviral vaccines has been demonstrated in both human and veterinary diseases [Szmuness et al, 1981;Bittle et al, 19821; structural studies on the gp340 component of MA have indicated that immunogenicity resides in the polypeptide moiety of the molecule [Morgan et al, 1983b;Epstein and Morgan, 19831, and the development of an EB virus vaccine can now proceed in the same direction.…”
Section: Discussionmentioning
confidence: 96%